HUBUNGAN PENGETAHUAN DAN SIKAP PEKERJA SPBU DENGAN PENGGUNAAN APD MASKER TERHADAP PAPARAN BENZENE DI KOTA LANGSA TAHUN 2014 - Aris Winandar; Tika Indiraswari (Serambi Saintia : Jurnal Sains dan Aplikasi, 2016)
Benzene is an organic chemical compound , colorless and flammable with a sweet odor .In use, benzene is a component dalam bensin and is an important solvent in the industry. The purpose of this study was to determine the relation of perception, knowledge, and attitudes of the Gas Station’s workers in using of self protective equipment masks exposure to benzene in the city of Langsa in 2014. The population in this study were all workers at the gas station filling petrol stations Langsa with a total of 102 people.The results showed that workers using of self protective equipment and masks as much as 17.6% and who did not wear as much as 82.4%, the knowledge of as low as 25.5%, which is higher by 74.5%, the negative attitude of 26.5%, and positive at 73.5%.This research can be concluded that there is the relation between knowledge by the use of a protective self equipment mask on workers at the gas station (P-value = 0,003 < 0,05), there was a correlation between perception by the use of a protective self equipment mask on workers at the gas station (P-value = 0,008< 0,05) ,there was a correlation between attitude to the use ofa protective self equipment mask on workers at the gas station(P-value = 0,006< 0,05). Key words : The protective self equipment mask, Refueling station, Benzene